Yeast Lipids Can Phase-separate into Micrometer-scale Membrane Domains - Klose, Christian (American Society for Biochemistry and Molecular Biology, 2010)
The lipid raft concept proposes that biological membranes have the potential to form functional domains based on a selective interaction between sphingolipids and sterols. These domains seem to be involved in signal transduction and vesicular sorting of proteins and lipids. Although there is biochemical evidence for lipid raft-dependent protein and lipid sorting in the yeast Saccharomyces cerevisiae, direct evidence for an interaction between yeast sphingolipids and the yeast sterol ergosterol, resulting in membrane domain formation, is lacking. Here we show that model membranes formed from yeast total lipid extracts possess an inherent self-organization potential resulting in liquid-disordered-liquid-ordered phase coexistence at physiologically relevant temperature. Analyses of lipid extracts from mutants defective in sphingolipid metabolism as well as reconstitution of purified yeast lipids in model membranes of defined composition suggest that membrane domain formation depends on specific interactions between yeast sphingolipids and ergosterol. Taken together, these results provide a mechanistic explanation for lipid raft-dependent lipid and protein sorting in yeast.